Pemanfaatan Video Eksperimen Sains sebagai Media Pembelajaran Interaktif IPA di MI Qurrota A'yun Garut - Povitasari (Idarotuna : Journal of Administrative Science, 2024)
By emphasizing the perspectives of both teachers and students, this study intends to investigate the usage of science experiment films as interactive learning materials in science courses at MI Qurrota A'yun Garut. Due to a lack of practical facilities and the predominance of lecture methods, students have a low conceptual comprehension of science materials, which is the basis of this study. The significance of learning experiences was thoroughly investigated using a qualitative methodology and a phenomenological design. Semi-structured teacher and student interviews, classroom observations, and learning activity documentation were used to gather data. Purposively, informants were chosen based on their active participation in the science education process via videos.Four major topics emerged from the data analysis: improving students' comprehension of scientific concepts, integrating Islamic values into science education, students cognitive and emotional engagement, and technical limitations and teachers adaptive solutions. It was demonstrated that experimental movies promoted active engagement in the classroom and helped students grasp complex ideas in a more engaging and tangible way. Instilling religious ideals and character was another way that teachers used videos. This study demonstrates how video content can be used to reinforce 21st-century abilities and mediate values in addition to serving as a learning aid.This study's implications include the necessity of legislative support for the provision of value-based learning media, the significance of teacher training in the use of contextual digital media, and the creation of a curriculum that is flexible enough to accommodate madrasah infrastructure. It is advised that more research be done to look at the long-term development and efficacy of media that is incorporated with students' local and spiritual contexts.